2016
DOI: 10.1017/s2040174416000623
|View full text |Cite
|
Sign up to set email alerts
|

Western diet in the perinatal period promotes dysautonomia in the offspring of adult rats

Abstract: The present study investigated the impact of a western diet during gestation and lactation on the anthropometry, serum biochemical, blood pressure and cardiovascular autonomic control on the offspring. Male Wistar rats were divided into two groups according to their mother's diet received: control group (C: 18% calories of lipids) and westernized group (W: 32% calories of lipids). After weaning both groups received standard diet. On the 60th day of life, blood samples were collected for the analysis of fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
2
3
1
3
Order By: Relevance
“…On analysing spontaneous baroreflex sensitivity, we found no differences between the groups, suggesting that baroreflex control, at least within the narrow range of the physiological variations of BP, is not altered in adult rats exposed to maternal dyslipidaemia. This result differed from another study showing a reduction in the baroreflex control in male offspring from dams fed a westernised diet ( 9 ) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…On analysing spontaneous baroreflex sensitivity, we found no differences between the groups, suggesting that baroreflex control, at least within the narrow range of the physiological variations of BP, is not altered in adult rats exposed to maternal dyslipidaemia. This result differed from another study showing a reduction in the baroreflex control in male offspring from dams fed a westernised diet ( 9 ) .…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement with other studies that used maternal high-fat diet as a model ( 9 ) , our study showed that male offspring exposed to maternal dyslipidaemia during pregnancy and lactation developed arterial hypertension at 90 d of age. It should be noted, however, that another study reported that offspring from dams exposed to hypercholesterolaemia during pregnancy did not exhibit hypertension in adulthood ( 38 ) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The pups from DLP dams had low birth weight and low weight at 21 days of age (2) in comparison to CTL male offspring. At 30 and 90 days of age, the bodyweight of male rat offspring was similar between groups (Table 2) Under baseline conditions, the LF range of SAP, DAP, MAP and HR were similar between CTL and DLP groups (Table 3).…”
Section: Re Sultsmentioning
confidence: 86%
“…Nutritional insults during pregnancy and/or lactation phases increase the risk in offspring for future arterial hypertension . Maternal dyslipidaemia is a condition characterized by high levels of total cholesterol (TC), triacylglycerol (TAG), low‐density lipoprotein (LDL) and decreased high‐density lipoprotein (HDL) .…”
Section: Introductionmentioning
confidence: 99%